â€TENTARA RAKYATâ€DI BANTEN SELATAN: KEKUATAN TERAKHIR PEMBELA TAN MALAKA - Suharto , Suharto (Jurnal Masyarakat dan Budaya, 2015)
After the first Dutch aggression, five Bambu Runcing(BR) Divisions were established inWest Java. One of them was posted at SanggabuanaMountain, Purwakarta, lead by Wahidin Nasution and, then, Khaerul Saleh. In the area, including this division, there were two military troops cooperated and united under Staff of Guerrilla Group of East JakartaTerritory, commanded by Mayor Sambas Atmadinata. However, the cooperation did not last for a long time, since armed contacts between Siliwangiand the BRoften occurred. BRwas pushed back and decided to continue activities in South Banten, where later, the groupâ€™s name becomes â€œTentara Rakyatâ€ (People Army). Here, they openly opposed the Government of the Republic of Indonesiabecause of several agreements arranged with the Dutch and targeted government officials, including police and the military, and killed them violently. These activities had feared people, therefore in the end of October 1949, the Indonesian National Army ended the actions whose based the movement was to continue Tan Malakaâ€™s ideas.